Proceedings of the First Asia Pacific Slope Stability in Mining Conference 2016
DOI: 10.36487/acg_rep/1604_24_cerro
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid rockfall barrier — new design methodology based on the Colorado full-scale test experience

Abstract: Hybrid rockfall barriers combine the energy absorption capabilities of a dynamic rockfall barrier with the reduced-maintenance advantages of drapery mesh. The aim of this innovative design is not to capture and stop the falling rocks, as the barriers tested according to ETAG 027 (EOTA 2008), but to contain the bounce of the rock and to drive it down the slope beneath the mesh draped down the slope face. Although this type of rockfall structure has already been applied worldwide, there is still a lack of knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They also studied the interaction between falling rocks and nets, as well as the distribution of energy loss and grid deflection. Cerro et al (2016) proposed a simplified analysis model that took the energy of falling rocks and slopes into account to design the attenuator system. It provided a basis for the designer to select model attenuator and suggested that there was no international guide to guide the design of attenuator system in any case.…”
Section: Experimental Researchmentioning
confidence: 99%
“…They also studied the interaction between falling rocks and nets, as well as the distribution of energy loss and grid deflection. Cerro et al (2016) proposed a simplified analysis model that took the energy of falling rocks and slopes into account to design the attenuator system. It provided a basis for the designer to select model attenuator and suggested that there was no international guide to guide the design of attenuator system in any case.…”
Section: Experimental Researchmentioning
confidence: 99%
“…Due to the capital importance of these structures in the risk mitigation process, it is fundamental to guarantee their operativity and functionality over time. In fact, the efficiency of these protection structures can be affected by several factors such as damages caused by previous impacts, debris accumulation on the nets, and ageing phenomena induced by the exposure to natural elements [8][9][10]. In this context, the monitoring activity of the protection structures plays a central role in the assessment of the structure conditions and planning of maintenance works.…”
Section: Introductionmentioning
confidence: 99%